Synthesis and fungicidal activity of 1, 1-diaryl tertiary alcohols. Issue 24 (15th December 2016) - Li, Xiuyun; Han, Xiaoqiang; He, Mengmeng; Xiao, Yumei; Qin, Zhaohai
Graphical abstract: Abstract: A series of 1, 1-diaryl tertiary alcohols and some of their dehydration derivatives were designed, synthesized and evaluated for their antifungal activities. Some compounds exhibited moderate inhibitory activities against seven plant pathogens at 50 μg/mL in vitro, compounds5 g and7 c displayed nearly the same or higher fungicidal activities against some certain plant pathogens compared with the lead compound pyrimorph. A qualitative structure-activity relationship (SAR) analysis revealed that the Cl substituent and its position at the pyridine ring were crucial for the compounds' activities. Specially, several compounds displayed 100% protection effect against wheat powdery mildew or cucumber anthrax at 400 mg/mL in vivo, which suggested that these compounds might be potential fungicidal candidates for certain plant diseases.